The Effect of Paraquat, Difenoconazole, and Butylphenyl Methylcarbamate (BPMC) on CO2 Emissions and Phenolic Acids in Peat Soil - Fitriyani, Indri Hapsari; Anwar, Syaiful; Hartono, Arief; Tjahyandari, Diah (JOURNAL OF TROPICAL SOILS, 2017)
Pesticides are widely used in agriculture, including on peat soil. The objective of this study was to analyze the effect of the application of paraquat, difenoconazole, and butylphenyl methylcarbamate (BPMC) on CO2 emissions and concentrations of phenolic acids in a peat soil. Peat soil sample was taken in District of Pulang Pisau, Central Kalimantan. The peat soil was applied with 1.89 mg kg-1 paraquat, 1.72 mg kg-1 difenoconazole and 1.65 mg kg-1 butylphenyl methylcarbamate (BPMC), then the soil was incubated for 1, 2, 4 , 5, 7, 10, 14, 21, 26 and 30 days. The results showed that the application of pesticides on peat soil increased CO2emission, and decreased CH4 emission and phenolic acid concentrations up to 30 days of incubation. The CO2 emmisions were derived from C of degraded pesticides and from C of phenolic acids, although the oxidation reaction was not accompanied by the change of soil pH.Â Keyword: CO2 emission, phenolic acids, butylphenyl methylcarbamate (BPMC), difenoconazole, paraquat, peat soil